Situation Report: Romania, 14 May 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. New Grand National Assembly Meets; Ceausescu Re-elected President / by Dan Ionescu Romanian-Soviet Gas Deals / by Vladimir Socor Soviet Gas Deliveries to Balkan Countries via Romania / by Vladimir Socor Student Apathy / by Carmen Cojocaru-Pompei